Language Barriers and Immigrant Health Production - Andrew Clarke; Ingo E. Isphording (Institute for the Study of Labor (IZA), 2015)
We study the impact of language deficiency on the health production of childhood migrants to Australia. Our identification strategy relies on a quasi-experiment comparing immigrants arriving at different ages and from different linguistic origins by utilising a measure of differences along a continuous range of linguistic distances. Our main results indicate a large negative effect of English deficiency on physical health that is robust to a range of different specifications. In the presence of considerable non-classical measurement error in self-reported language proficiency, our results provide lower and upper bounds for the true effect of English deficiency on health of one half and a full standard deviation in the health score respectively. The empirical analysis is framed in terms of a Grossman model which indicates a twofold role of language skills in health production: language deficiency directly affects the efficiency of health production and indirectly affects access to health inputs. We provide some suggestive evidence on the relative importance of these distinct roles.
Keywords: F22; I12; J24; J61; 330; international migration; language skills; health